Millimeter wave wireless communications for fifth generation (5G) - Rappaport, Theodore S., 1960- (LiveLessons., 2019)
"In this video training, Professor Rappaport starts by providing an overview to the basics in ultrawideband digital communications. He then introduces topics such as MmWave Propagation, ray tracing, Channel Models, and Antennas. He ends the first section with a discussion on RF and Analog Circuits and Systems for mmWave transceivers. In the second section, Professor Rappaport covers Ultrawideband Baseband circuits, Beamforming, Networking, and device discovery. He describes Modulation, Coding and Relay approaches for mmWave wireless. Finally, he ends the program with a discussion of current 60 GHz mmWave wireless LAN standards."--Resource description page